Subversive Activities of Hungarian and Polish Sabotage Groups in Carpathian Ukraine (1938–1939) - Vehesh, I.; Vehesh, M. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2022)
The article, based on archival and published documents, attempts to highlight the international situation of the Czechoslovak Republic and Transcarpathia on the eve of World War II. It proves that Hungary, throughout the interwar period, pursued an aggressive irredentist policy aimed at destabilizing Czechoslovakia and returning “its original territories”. This revanchist activity culminated in 1938–1939, when the Hungarian government sent diversion groups to Carpathian Ukraine, trying to destabilize the domestic political situation in the region. A similar subversive operation was carried out by Poland, which sought to establish a common Hungarian-Polish border by completely eliminating Czechoslovakia. The authors argue that a “hybrid war” was waged against young Carpathian Ukraine and in mid-March 1939 it escalated into open intervention and occupation of the entire territory of the region. A. Voloshyn’s government together with the Czechoslovak troops made a lot of efforts to protect the settlements of Carpathian Ukraine from the destructive actions of enemy saboteurs. The formed divisions of the Carpathian Sich and the Ukrainian gendarmerie were involved in the defense of the borders. Some parallels can be drawn with the events of 2014 in Ukraine, when Russian troops annexed Crimea and occupied part of Donetsk and Luhansk regions. In 1938–1939, the governments of Hungary and Poland assured the world community that their troops did not exist in Transcarpathia. Similar is the position of the leadership of the Russian Federation concerning the events of 2014–2021 in Ukraine.